(untitled) (Metallurgy and Foundry Engineering, 2009)
In the paper, results of microstructure and hardness examination of cold-worked alloyed steel AISI 316L are presented. In addition, determined was corrosion resistance of the steel in the Ringer solution. Corrosion tests were performed after cold working with 10, 20, 30, 40 and 50% ratio. Potentiodynamic tests included recording polarisation curves as well as determining corrosive potential and corrosive current for various cold working ratios. Cross-sections of the specimens after corrosion tests were observed and analysed using a scanning microscope.